The Chief Data Officer's playbook - Carruthers, Caroline; Jackson, Peter (Data officer) (Facet Publishing, 2018)
The new and rapidly expanding role of the Chief Data Officer (CDO) is of significant interest and relevance to organisations and data professionals internationally. Written by two practicing CDOs, this new book offers a jargon-free, practical guide to making better decisions based on data. Content covered includes: why does any organisation need a CDO? the secret ingredients of the successful CDO avoiding the hype cycle building the CDO team who leads the technology? the CDO and data governance: enablement not red tape. This book will offer key insight for CDOs looking to understand their position better, for aspiring CDOs and data officers looking at career progression, for those recruiting CDOs, and offers essential knowledge for anyone else operating in the current data environment